THE EFFECT OF EXCESSIVE SETTING TIME, LONG DAMAGE OF THE MACHINE, TIME OF PACKAGING PACKAGES STOPPED TO PRODUCTION OPERATIONAL COSTS: STUDY IN LINE 8A PT XYZ FARMA Tbk - A Ashwatu Nida Dipajana; Iha Haryani H (Sekolah tinggi ilmu ekonomi pemuda, 2020)
This study aims to determine the effect of excess machine setting time, machine breakdown time, time for packaging lines to stop, on production operating costs and which factors are most dominant in influencing production operating costs. This research uses a quantitative descriptive method approach. The place of research is at PT. XYZ Farma on line 8A. The research sample consisted of 22 data records from a population of 450 data records. Data collection techniques are observation techniques, event recording and documentation. The results showed the influence of excessive setting time, machine damage time, packaging line time stalled against operational costs of production. This is demonstrated by using AMOS, the value of C.R (Critical Ratio) exceeds the critical value ± 1,717. The value of C.R for each variable is the excessive machine setting time, the length of time the machine is damaged, and the time of the packaging line has stalled towards the operational cost of production is 2,850; 10, 913; 5,330. Based on AMOS Standardized Regression Weight Output statistical calculations show that the duration of damage to the machine provides the greatest contribution in increasing the operational costs of production. This is indicated by the estimated coefficient value of the largest engine damage time which is 82.1%. So it can be concluded that the influence of excess engine setting time, machine breakdown time and time of the packaging line has stalled to the operational costs of production with the variable length of engine damage giving the greatest contribution.